Downregulated long non-coding RNA LINC00899 inhibits invasion and migration of spinal ependymoma cells via RBL2-dependent FoxO pathway. Issue 19 (2nd October 2019) - Chen, Qun-Bang; Li, Zhao-Hui; Fu, Yao; Lv, Ning-Ning; Tian, Nan; Han, Liang; Tian, Yu
ABSTRACT: This study is aimed to clarify the potential role of lncRNA LINC00899 in invasion and migration of spinal ependymoma cells through the FoxO pathway via RBL2. Spinal ependymoma related chip data (GSE50161 and GSE66354) was initially downloaded and differentially expressed lncRNAs were screened out. Fifty-eight cases of spinal ependymoma and normal ependymal tissues were collected. The effects of LINC00899 and RBL2 on the spinal ependymoma cell migration and invasion were determined using the third generation spinal ependymoma cells and transfection with LINC00899 vector, siRNA-LINC00899 and siRNA-RBL2. The expression of LINC00899, pathway and cell proliferation- and apoptosis-related factors was determined. Finally, we also detected cell proliferation, migration, invasion, cycle and apoptosis after transfection. Our results showed that LINC00899 was up-regulated in spinal ependymoma and RBL2 was confirmed as a target gene of LINC00899 and found to be involved in regulation of FoxO pathway. LINC00899 expression increased in spinal ependymoma tissues whereas RBL2 expression decreased. Moreover, we found that siRNA-LINC00899 could elevate RBL2, p21, p27 and Bax levels, decrease FoxO, Bcl-2, Vimentin, Annexin levels, reduced cell proliferation, migration and invasion and enhanced apoptosis. Taken together, our study suggests that down-regulated LINC00899 exerts anti-oncogenic effects on spinal ependymoma via RBL2-dependent FoxO, which provides a novel therapeutic target for the treatment of spinal ependymomas.